Islamophobia: differences across Western and Eastern community residents toward welcoming Muslim tourists - Al-Ansi, Amr; Chua, Bee Lia; Kim, Chang Sik; Yoon, Hyejin; Han, Heesup (Elsevier, 2022)
The study has discussed the potential effect of islamophobia and its obstacle role in creating an unpleasant travel experience for the Muslim tourism market. The study compares non-Muslim (Western) and (Eastern) community residents regarding their willingness to host international Muslim tourists. Data was obtained using interviews and two separated online surveys (Western = 340 and Eastern = 443). The results revealed both similarities and dissimilarities across groups for Islamic culture knowledge, attitude, perceived benefits, feelings about Muslim tourists, image, and future intention. The study helps us know how to address the islamophobia issue and sustain their halal tourism services.